TASAVVUFDA ISHQ, SAMO VA MA’RIFAT: TASAVVUFIY TAFAKKUR HAMDA ADABIY-ESTETIK AN’ANALARNING SHAKLLANISHI (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2026)
This text analyzes the spiritual and philosophical essence of Sufism, its inextricable connection with literature, music and aesthetic thought. It reveals the role of the sky, dhikr, poetry and mystical symbols as a means of spiritual education.